Construction of High-Density Tissue Microarrays at Low Cost by Using Self-Made Manual Microarray Kits and Recipient Paraffin Blocks - Choi, Chang Hwan (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2012)
BACKGROUND: Advances of tissue microarray (TMA) technology have enabled simultaneous in situ analysis of biomarker expression in a large number of archived pathology specimens. However, the relatively high cost of TMA construction may hamper many researchers from using this essential tool of modern pathology research. We discuss methods for making TMA kits and recipient blocks for manual construction of high-density TMAs at low cost. METHODS: Ordinary cannula piercing needles, hypodermic needles, bone marrow biopsy needles, metallic ink cartridges of ballpoint pens, and disposable skin biopsy punches were used to construct self-made manual TMA kits. The recipient blocks were manufactured by boring holes in the conventional bare paraffin blocks. A mini electric hand drill and a microcompound table assembled on a drill stand were used to maximize the capacity of the recipient blocks. RESULTS: By using TMA kits made from cannula piercing needles (16- and 18-gauge), it was possible to construct TMAs with 1 mm×140 cores, 0.6 mm×320 cores, 2 mm×70 cores, 3 mm×35 cores, and 5 mm×12 cores. The capacity of the recipient blocks could be dramatically increased by drilling holes. CONCLUSIONS: Construction of TMAs using self-made TMA kits is an inexpensive alternative to construction of TMAs using commercial devices.